PERKEMBANGAN REGULASI PENINGKATAN NILAI TAMBAH NIKEL DI INDONESIA - Arif Setiawan; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
One of mining industry characteristics is non renewable, therefore its management should be optimal, efficient and environmentally oriented. Indonesian government has established the mining law as a main regulation in carrying out mineral and coal mining activities. The regulation related to mining industry was Act No. 11/1967, which then replaced by Act No. 04/2009. Implementing rule of the Act No. 04/2009 is regulated through a Government Regulation (PP). In order to implement this government regulation, a Minister Regulation is then need to be issued. The main objective of this research is to know the development of the downstream mining industry related to increasing value added, especially nickel. The method used in this study is a descriptive method that describes secondary data in the form of documentation obtained from various sources. The results shows that the implementation of Act No. 04/2009 has ogbligated the maning companies to built their smelters to run mineral processing and metal refining in five years, in which it can increase value added of minerals, including nickel. Therefore, according to the act, in 2014 raw ore exports should be banned. This condition results in a decrease of raw ore export. The construction of a smelter is used to process and purify nickel with levels above 2%. However, in Indonesia there is still nickel ore with levels below that level. Therefore, Ministerial Regulation No. 05/2017 was issued to overcome this problem, which is currently being replaced by ministerial regulation No. 25/2018.